1987
DOI: 10.1073/pnas.84.11.3555
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of full-length cDNA clones coding for cholinesterase from fetal human tissues.

Abstract: To study the primary structure and regulation of human cholinesterases, oligodeoxynucleotide probes were prepared according to a consensus peptide sequence present in the active site of both human serum pseudocholinesterase (BtChoEase; EC 3.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 29 publications
6
85
0
1
Order By: Relevance
“…Doctor [6][7][8][9][10][11], as have partial sequences of AChEs isolated from human erythrocytes [12,13], human brain [14], and bovine brain [15]. Pharmacological studies and enzyme kinetic studies with these enzymes, including multiple molecular forms, have demonstrated that they possess similar catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Doctor [6][7][8][9][10][11], as have partial sequences of AChEs isolated from human erythrocytes [12,13], human brain [14], and bovine brain [15]. Pharmacological studies and enzyme kinetic studies with these enzymes, including multiple molecular forms, have demonstrated that they possess similar catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…3) is also hydrophilic and interestingly, exhibits complete amino acid identity. This hydrophilic insertion appears to be unique to insect acetylcholinesterases and is absent in both nematode Ace-1 [27] and vertebrate cholinesterase sequences [28][29][30][31][32][33][34][35], lending support to the hypothesis that proteolytic cleavage of the AChE precursor protein could be a common mechanism in insects [25,26]. Boxed residues indicate sequence identity.…”
Section: Cloning and Sequence Analysis Of Aedes Ace Genementioning
confidence: 92%
“…Another conserved feature of the Aedes sequence is the six amino acid consensus sequence FGESAG surrounding the active site serine. This peptide motif is common to all vertebrate [28][29][30][31][32][33][34][35] and invertebrate [24][25][26][27] cholinesterases studied to date. As noted by Hall and Malcolm [25], both the putative signal peptide domain and C-terminus of the insect AChE protein are [25,26] is the hydrophilic region located between Arg-148 and Pro-180 in Drosophila ACHE, where endoproteolytic cleavage of the 75KDa precursor protein into two non-covalently linked polypeptides takes place [37].…”
Section: Cloning and Sequence Analysis Of Aedes Ace Genementioning
confidence: 99%
“…In Asia, most of the deaths are reported due to snake's bite especially of the members of family Elapidae. Family Elapidae's venom contain large amount of acetylcholinesterase (AchE) which causes the acetylcholine's (physiological events controller) inactivation by the enzymatic interruption (Prody et al, 1987;Dave et al, 2000).…”
Section: Introductionmentioning
confidence: 99%